Green threads: Unveiling sustainable fashion preferences among Indonesian gen Z consumers - Anisah, Tiara Nur; Luthfiana, Della Nanda; Kumar, Vikas; Ernestivita, Gesty; Harnaji, Bimo; Najmudin, Mohamad (Asian Management and Business Review, 2024)
The textile industry has been a critical driver of global economic growth in recent decades. However, this growth is inextricably linked to its environmental impact. The textile industry causes significant environmental issues, including water pollution from dyes, high water usage, and greenhouse gas emissions. Understanding these specific environmental issues highlights the need to explore solutions, such as using eco-friendly clothing. This study aims to identify the factors that influence generation Z consumers’ preferences for eco-friendly clothing products in Indonesia by adopting the theoretical framework of the Information-Motivation-Behavioural Skills (IMB) model. The IMB model was chosen for its comprehensive approach to explaining how information and motivation, combined with behavioral skills, drive consumer actions, making it suitable for analyzing sustainable purchasing behavior. 201 generation Z respondents in Indonesia completed the survey using consecutive sampling. The data was then analyzed using structural equation modeling (SEM). The results showed a positive and significant influence between green self-concept and subjective norm on the purchase intention of environmentally friendly clothing. However, green clothing knowledge’s effect on purchase intention was not statistically significant. Further results found that green clothing self-efficacy can mediate the influence of green self-concept and subjective norm on green clothing purchase intention. However, green self-efficacy has not been proven to mediate the effect of environmental apparel knowledge on purchase intention.